Single-Locus and Multi-Locus Genome-Wide Association Studies in the Genetic Dissection of Fiber Quality Traits in Upland Cotton (Gossypium hirsutum L.) - Li, Chengqi; Fu, Yuanzhi; Sun, Runrun; Wang, Yuanyuan; Wang, Qinglian (Frontiers in Plant Science, 2018)
Improving fiber quality is a major breeding target in Upland cotton (Gossypium hirsutum L.). To address this issue, 169 diverse accessions genotyped by 53,848 high-quality single-nucleotide polymorphisms (SNPs) and phenotyped in four environments were used to conduct genome-wide association studies for fiber quality traits using three single-locus and three multi-locus models. As a result, 342 quantitative trait nucleotides (QTNs) controlling fiber quality traits were detected. Among these QTNs, 84 were simultaneously detected in at least two environments or by at least two models, including 29 for fiber length, 22 for fiber strength, 11 for fiber micronaire, 12 for fiber uniformity, and 10 for fiber elongation. Meanwhile, nine QTNs with the sizes (R2) of more than 10% were simultaneously detected in at least two environments and between single- and multi-locus models, including TM80185 (D13) for fiber length, TM1386 (A1) and TM14462 (A6) for fiber strength, TM18616 (A7), TM54735 (D3) and TM79518 (D12) for fiber micronaire, TM77489 (D12) and TM81448 (D13) for fiber uniformity, and TM47772 (D1) for fiber elongation. This indicates the possibility of marker-assisted selection in future breeding programs. Among 455 genes within the linkage disequilibrium regions of the nine QTNs, 113 are potential candidate genes and four are promising candidate genes. These findings reveal the genetic control underlying fiber quality traits and provide insights into possible genetic improvements in Upland cotton fiber quality.